Participação nos lucros ou resultados nas empresas estatais federais: questões emergentes, problemas e desafios - Suzuki, Juliana Akiko Noguchi (2010)
This dissertation is an exploratory case study about the State Owned Enterprises Coordination and Governance Department (Departamento de Coordenação e Governança das Empresas Estatais – DEST) of the Ministry of Planning, Budget and Management of the Brazilian Federal Government. Specifically, it is about how the organization has been analyzing and approving profit sharing proposals from state owned enterprises. Four companies were sampled through qualitative methods, all of which presented proposals with reference to the year of 2008. Information was gathered from the proposals, official documents, current legislation and interviews with former and current DEST representatives, and analyzed with reference to agency theory literature, as well as performance measurement in the public sector, administrative reforms in Brazil, from the standpoint of view of new institutionalism. The following accomplishments were made: (i) DEST and the current legislation were analyzed as the institutions mediating the proposals and the approvals of the profit sharing programs; (ii) identification and analysis of which would be the real preferences from DEST related to this subject; (iii) general inferences about the main characteristics of the profit sharing proposals coming from the state owned enterprises in Brazil; (iv) identification and analysis of the results (the approvals) being produced by the institutions in focus; (v) discussion of the factors limiting or facilitating the functioning of those institutions; and (vi) assessment of how the interviewees perceive the profit sharing programs as far as an incentive to increase productivity. As a result, it concludes that (i) the approvals from DEST reflect only part of its real preferences related to the design of those programs and that (ii) DEST’s performance is different between the main aspects that constitute profit sharing programs (indicator selection, goal setting, budget constraints and way of program budget distribution).